Влияние тетрадецилтриметиламмоний бромида на состояние ферментной системы антиоксидантной защиты тканей черноморского моллюска Mytilus galloprovincialis Lam. - Гостюхина, О.Л.; Солдатов, А.А; Головина, И.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The content of lipid peroxidation (LP) products and antioxidant (AO) enzyme complex state in hepatopancreas, gills, and foot of the Black Sea mussel Mytilus galloprovincialis Lam. are investigated under the inﬂuence of cationic surfactant tetradecyltrimethylammonium bromide (TDTMA). It has been determined that the ТDТМА has the direct damaging effect on the peri- pheral tissues of mussels, i. e. gills and foot. Increasing the TBA-active products level conﬁrms this phenomenon. The system SOD-catalase plays the key role in the AO defense processes under the oxidative stress caused by the detergent. The glutathione peroxide system of peri- pheral tissues of mollusks is directed to increasing the glutathione level. The state of internal organs (hepatopancreas) has not been changed under the detergent inﬂuence.